AKUNTABILITAS PEMERINTAH DESA DALAM PENGELOLAAN ANGGARAN DANA DESA DI DESA TALAWE - Riska Sabir; Ahmad Mustanir; Akhmad Yasin; Firman Firman; Wahyudi Sofyan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
The purpose of this study is to determine the accountability of the village government in the management of village funds in Talawe Village, Watang Sidenreng District, Sidenreng Rappang Regency, then to determine the factors that affect Village Government Accountability in Village Fund Management in Talawe Village, Watang Sidenreng District, Sidenreng Rappang Regency.The research method used in this research is descriptive quantitative research, while the population of this study is 308 people, while the research sample is 79 people. The data collection technique used in this research is to use technique (1). Observation, (2). Questionnaire, (3). Documentation. The collected data was then analyzed using a frequency table and using the SPSS 21 application.The results of this study indicate that the accountability of the village government in Sidenreng Rappang Regency can be categorized as good with a percentage of 70.5%, while the Accountability Factors of the Talawe Village Government, Watang Sidenreng District, Sidenreng Regency is not good with a percentage of 46.6%.